The Role of Brand Image as a Mediator of the Relationship Between Viral Marketing and Word of Mouth on the Purchase Decision of the Sumenep Online Noodle Home Business - Vitamami Mardatillah Imamah; Rachmad Hidayat; Sri Rahayu (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the role of brand image as a mediator in the relationship between viral marketing and word of mouth on purchasing decisions for online noodle home businesses in Sumenep. The background of this study is based on the implementation of viral marketing, the effectiveness of which is still unknown. Word of Mouth The extent to which the brand image formed among consumers of Mie Daring Sumenep cannot be ascertained in terms of its contribution in influencing purchasing decisions and the emergence of a gap in brand perception among potential consumers. The number of samples in this study was 100 people. The data analysis technique in this study used Partial Least Square (PLS) method. The results of the study show that Viral Marketing has a significant influence on Buying decision, either directly or indirectly through Brand Image, which emphasizes the important role of viral strategies in shaping positive brand images and driving consumer decisions. Meanwhile, Word of Mouth does not have a direct significant influence on purchasing decisions, but has been proven to have a significant influence on Brand Image, so that it can indirectly influence purchasing decisions by strengthening brand image. Furthermore, Brand Image proven to have a significant influence on Buying decision.